Cloud Point Temperature, Thermal and Dielectrical Behaviors of Thermosensitive Block Copolymers Based N-Isopropylacrylamide - Ilboga, Serzen; Pekdemir, Ersin; Coskun, Mehmet (Pleiades Publishing Ltd, 2019)
The diblock and triblock copolymers were synthesized by chain extending on poly(N-isopropyl-acrylamide) (H-PNIPA) with HO-CH2CH2- and -Cl end group obtained from atom transfer radical polymerizaiton technique by aid of the same technique, using ethylmethacrylate (EMA), 2-hydroxypropyl methacrylate (HPMA), N,N-dimethylacrylamide (DMA) and benzylmethacrylate (BMA) as comonomers. Number average molecular weight of H-PNIPA homopolymer and the diblock copolymers, H-PNIPA-b-PEMA, H-PNIPA-b-PHPMA, H-PNIPA-b-PDMA were estimated as 1960, 3990, 3110 and 4040 g/mol, from H-1 NMR spectra. Structure of the copolymers were characterized by FTIR and H-1 NMR techniques. TGA curves showed that the thermal stability of the diblock and triblock copolymers decrease comparing to H-PNIPA. The T-g temperatures of the polymers, H-PNIPA, the diblock copolymers, and triblock copolymers, H-PNIPA-b-PDMA-b-PEMA and H-PNIPA-b-PDMA-b-PBMA were predicted from the DSC curves, as 130 degrees C, in range of 105-115, and 90 and 100 degrees C, respectively. The dielectric constant decreased slightly in the frequency range between 0.1 and 2.0 kHz at room temperature. Cloud point temperature (CPT) values of H-PNIPA homopolymer and the block copolymers were determined using UV-Vis, turbidimetry and viscometer techniques in aqueous solution. The CPTs found by three different techniques for each polymer were close to each other. In the diblock and triblock copolymers, some differences in CPTs were observed according to comonomer and these were discussed.
Keywords: Drug-Delivery; Thermoresponsive Polymers; Aqueous Chromatography; Sensitive Hydrogels; Molecular-Weight; Poly(N-Isopropylacrylamide); Salt